(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
In this paper, the authors introduced a new operator by using a generalized Mittag-Leffler function. Also, the authors defined the meromorphic subclasses associated. Finally calculated inclusion relation.